Reasons why most nurse educators in nursing colleges do not use lesson plans at Malamulo College of nursing. - Banda, Jessie (Kamuzu University of Health Sciences, 2022)
This was a qualitative study aimed at finding out the reasons why most nurse educators in nursing colleges do not use lesson plan when delivering lessons to student nurses. The study was conducted at Malarnulo College of Health Sciences, nursing department. I'he sample consisted of ten nurse educators. "The specific objectives were, to assess the knowledge of nurse educators about lesson plans. to explore the views of nurse educators about the use of lesson plans and to analyse the experiences of nurse educators on the use of lesson plan. Purposive sampling was used to identity the study subjects. Data was collected using an interview guide developed from the specific objectives with open-ended and closed-ended questions and was analysed manually. Purposive sampling was used to identity the study subjects. Data was collected using an interview guide developed from the specific objectives with open-ended and closed-ended questions and was analysed manually.